BS EN IEC 61755-3-5. Fibre optic interconnecting devices and passive components. Connector optical interfaces. Part 3-5. Connector parameters of non-dispersion shifted single mode physically contacting fibres. Non-angled 2, 5 mm and 1, 25 mm diameter cylindrical composite ferrule using Cu-Ni alloy as fibre surrounding material (22nd January 2021) - British Standards Institution,
No abstract available